2011
DOI: 10.1371/journal.pone.0018095
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multiple HPV Types on Spermatozoa from Human Sperm Donors

Abstract: Human papillomaviruses (HPV) may cause sexually transmitted disease. High-risk types of HPV are involved in the development of cervical cell dysplasia, whereas low-risk types may cause genital condyloma. Despite the association between HPV and cancer, donor sperm need not be tested for HPV according to European regulations. Consequently, the potential health risk of HPV transmission by donor bank sperm has not been elucidated, nor is it known how HPV is associated with sperm. The presence of 35 types of HPV wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 28 publications
4
48
0
7
Order By: Relevance
“…We detected HPV-DNA, HPV-E4 and HPV-L1 in exfoliated keratinocytes present in some HPV16-positive semen samples, indicating the presence of HPV viral particles. In addition, we detected HPV-DNA on spermatozoa using FISH, which is in line with previous studies (8,9,21), but no HPV-L1. Although the number of additionally tested semen specimens is limited, the findings suggest that these FISH signals represent free viral DNA, released from terminally differentiated, exfoliated keratinocytes that adhere to sperm heads.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We detected HPV-DNA, HPV-E4 and HPV-L1 in exfoliated keratinocytes present in some HPV16-positive semen samples, indicating the presence of HPV viral particles. In addition, we detected HPV-DNA on spermatozoa using FISH, which is in line with previous studies (8,9,21), but no HPV-L1. Although the number of additionally tested semen specimens is limited, the findings suggest that these FISH signals represent free viral DNA, released from terminally differentiated, exfoliated keratinocytes that adhere to sperm heads.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported the prevalence of HPV in semen, ranging from 2% to 31% in asymptomatic men (7,8,10,22,23), 16%-26% in semen donors (21,24), and 3%-36% in fertility clinic attendees (7,10). The reported prevalence of HPV in semen in populations of asymptomatic men corresponds with the prevalence of 27% found in our study using GP5þ/6þ PCR.…”
Section: Discussionsupporting
confidence: 86%
“…In men HPV sperm infections can be long-lasting (24 months) and are frequently associated with anti-sperm antibodies that may further reduce male fertility [5]. The presence of HPV virions that can bind two distinct sites along the equator of the spermatozoa's heads [5,6,7,8] may not only have a detrimental effect on sperm parameters [6,8,9] but also on gamete interaction, since in vitro experiments have demonstrated that spermatozoa can not only transfer HPV virions [10] to the oocyte, but the transferred HPV virions also induce stage-specific maturation arrest in infected embryos [11]. In untreated women with transient HPV infections, the median number of months between the first negative HPV measurement and the viral load maximum and the last HPV-negative measurement, irrespective of the HPV type, was 15.7 months and 11.9 months, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, las muestras de orina han sido ampliamente estudiadas por sus ventajas como método de muestreo; sin embargo, los resultados no han sido totalmente satisfactorios 43 . Además, se han realizado estudios para la identificación de VPH en muestras de semen, por las implicancias que el VPH podría tener sobre la funcionalidad, la concentración, movilidad y viabilidad de los espermatozoides 44 . Debido a que un mismo individuo puede ser positivo para VPH en varios sitios anatómicos al mismo tiempo, uno de los desafíos es determinar la combinación de muestras más representativas y accesibles que no alteren la prevalencia estimada y que, a su vez, tengan aceptación entre los hombres.…”
Section: Tipos De Muestras Para La Detección De Vph En Hombresunclassified